Validity and reliability of the V-cut dribbling test in young basketball players - Jòdar-Portas, A.; López-Ros, V.; Prats-Puig, A.; Beltran-Garrido, J. V.; Madruga-Parera, M.; Romero-Rodríguez, D.; Gonzalo-Skok, O.; Sinclair, G.; Font-Lladó, R. (International Journal of Sports Physiology and Performance, 2023)
Purpose: Change of direction while dribbling appears to be of interest for on-court performance in basketball. The study aim was to assess the validity and reliability of the V-cut dribbling test (VcutBk) in young basketball players.